2011
DOI: 10.3856/vol39-issue3-fulltext-1
|View full text |Cite
|
Sign up to set email alerts
|

Non enzymatic antioxidant photoprotection against potential UVBR induced damage in an Antarctic diatom (Thalassiosira sp.)

Abstract: ABSTRACT. In January 1999, unialgal cultures of the diatom Thalassiosira sp., solate from natural phytoplankton assemblages from Potter Cove, Antarctica, were exposed to solar ultraviolet radiation (UVR, 280-400 nm) in order to study the long-term acclimation of this species. Ultraviolet radiation B (UVBR, 280-315 nm) inhibited the growth rate during the first and second days of exposure. No UVBR inhibition was observed on the third day. The initial content of α-tocopherol (13 pmol (10 4 cell)) showed a marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
4
0
2
Order By: Relevance
“…In the diatom Thalassiosira sp., isolated from natural phytoplankton assemblages from Potter Cove (Antarctic Peninsula) α-tocopherol showed a marked decrease during the exponential growth phase after exposure to solar UV-R, while the initial content of β-carotene did not show significant differences over time [ 312 ]. In addition, MAA production increased, suggesting that for this species photoprotection against UV-induced damage is characterized by short-term consumption of α-tocopherol and longer-term synthesis of MAAs.…”
Section: Uv Photoprotection In Marine Organisms: Antarctic and Nonmentioning
confidence: 99%
“…In the diatom Thalassiosira sp., isolated from natural phytoplankton assemblages from Potter Cove (Antarctic Peninsula) α-tocopherol showed a marked decrease during the exponential growth phase after exposure to solar UV-R, while the initial content of β-carotene did not show significant differences over time [ 312 ]. In addition, MAA production increased, suggesting that for this species photoprotection against UV-induced damage is characterized by short-term consumption of α-tocopherol and longer-term synthesis of MAAs.…”
Section: Uv Photoprotection In Marine Organisms: Antarctic and Nonmentioning
confidence: 99%
“…Hernando et al [47] showed that photoprotection against UV-induced damage is characterized by short-term consumption of -T and long-term synthesis of mycosporine-like amino acids (MAAs) in an Antarctic diatom Thalassiosira sp. The UV-B damage/repair ratio during long-term exposure involves the combined action of several endogenous factors within the cell, with MAAs synthesis being the most effective factor.…”
Section: Uv Radiation (Uv-r) Exposurementioning
confidence: 99%
“…Therefore, the attenuation of UVBR in the mesocosms cannot explain the lack of observed UVBR effects during our study. Hernando et al (2002Hernando et al ( , 2011 found that the phytoplankton community produced photoprotective pigments such as mycosporine-like amino acids (MAAs) or antioxidants prior to their UVBR exposure experiments. This allowed the community to reduce the negative effects of UVBR.…”
Section: Uvbr Effects On the Beagle Channel Microbial Communitymentioning
confidence: 99%